Optimalisasi Peran Nazhir dalam Pengembangan Wakaf Produktif - Suyanto Suyanto; Wulpiah Wulpiah (Universitas Islam Raden Rahmat, 2025)
The success of Islamic countries shows that waqf can contribute to overcoming economic problems. In Indonesia, waqf management is regulated through Law No. 41 of 2004, Government Regulation No. 25 of 2018, and Minister of Religious Affairs Regulation No. 4 of 2009. The local government and the Belitung Regency BWI are actively developing productive waqf by optimising the role of nazhir. This study uses a case study method with observation, documentation, and interviews with five key informants from the BWI, religious leaders, community leaders, and the nazhir forum. Data analysis refers to Miles and Huberman. The results show that the BWI's nazhir guidance mechanism covers two aspects. First, the recruitment pattern is through letters to village heads and the Religious Affairs Office (KUA), but it is still limited to the village and mosque levels. Second, guidance is carried out through basic socialisation without special certification. Optimising the role of nazhir includes regeneration, technical training, and increasing waqf literacy. BWI Belitung needs to revitalise its management and synergise with Ministry of Religious Affairs programmes such as waqf incubation and the millennial literacy movement.